Modified nodal stage of esophageal cancer based on the evaluation of the hazard rate of the negative and positive lymph node - Jinling Zhang; Hongyan Li; Liangjian Zhou; Lianling Yu; Fengyuan Che; Xueyuan Heng (BMC Cancer, 2020)
Abstract Background The study aimed to propose a modified N stage of esophageal cancer (EC) on the basis of the number of positive lymph node (PLN) and the number of negative lymph node (NLN) simultaneously. Method Data from 13,491 patients with EC registered in the SEER database were reviewed. The parameters related to prognosis were investigated using a Cox proportional hazards regression model. A modified N stage was proposed based on the cut-off number of the re-adjusted ratio of the number of PLN (numberPLN) to the number of NLN (numberNLN), which were derived from the comparison of the hazard rate (HR) of numberPLN and numberNLN. The modified N stage was confirmed using the cross-validation method with the training and validation cohort, and it was also compared to the N stage from the American Joint Committee on Cancer (AJCC) staging system (7th edition) using Receiver Operating Characteristic (ROC) curve analysis. Results The numberPLN on prognosis was 1.042, while numberNLN was 0.968. The modified N stage was defined as follows: N1 stage: the ratio range was from 0 to 0.21; N2 stage: more than 0.21, but no more than 0.48; N3 stage: more than 0.48. The log-rank test indicated that significant survival differences were confirmed among the N1, N2 and N3 sub-groups of patients in the training population. The difference of all the patients using the modified N stage method were more significant than AJCC N stage. The result of ROC analysis indicated that the modified N stage could represent the N stage of EC more accurately. Conclusion The modified N stage based on the re-adjusted ratio of numberPLN to numberNLN can evaluate tumor stage more accurately than the traditional N stage.